Structural characterization and anti-inflammatory effects of an arabinan isolated from Rehmannia glutinosa Libosch. (1st March 2023) - Zhang, Han; Yue, Yimin; Zhang, Qian; Liang, Lanyuan; Li, Chuanqiu; Chen, Ying; Li, Wei; Peng, Mingming; Yang, Mengru; Zhao, Mantong; Cao, Xia; Zhong, Luyang; et al.
Abstract: Considering that natural polysaccharides are potential anti-inflammatory agents, in this study, an arabinan (RGP70–2) was isolated and purified from Rehmannia glutinosa Libosch. ( R. glutinosa ) and its structure was characterized. RGP70–2 was a homogeneous polysaccharide with a molecular weight of 6.7 kDa, with the main backbone comprising →5)- α -L-Ara f -(1→, →3)- α -L-Ara f -(1→, →2, 3, 5)- α -L-Ara f -(1→, and →2, 5)- α -L-Ara f -(1 → linkages and the side chain comprising an α -L-Ara f -(1 → linkage. In vivo experiments showed that RGP70–2 inhibited ROS production and downregulated the expression of pro-inflammatory cytokines (TNF- α, IL-1 β, and IL-6). In vitro experiments showed that RGP70–2 decreased levels of pro-inflammatory cytokines, inhibited ROS production, and attenuated NF- κ B-p65 translocation from the cytoplasm to the nucleus. Our results showed that RGP70–2 may delay inflammation by regulating the ROS-NF- κ B pathway. Thus, RGP70–2 has potential applications as an anti-inflammatory agent in the biopharmaceutical industry. Graphical abstract: Unlabelled Image